(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2022)
This reading suggests to deal with what has been denominated as holy space, understanding it as the literary representation of beliefs and and its ritual manifestations present in the works of Ruth Fuentealba Millaguir, Cherrufe (2008) and Ana Maria Gonçalves Um defeito de cor [2006] (2009). We propose that this space emerges within the Afro-Brazilian and Mapuche narrative a female individual that related with symbolic system of its community interweave the traces of genre, race and sexuality in the subjective constitution. In addition, we claim that through the link between women and the sacred, the subjectivity that emerges in the works analyzed is presented as preserving and reproducing the culture and their most precious knowledge, indispensable for the individual and collective survival of their peoples.